Pengaruh Diameter Filter Terhadap Hasil Mesin Pencacah Plastik 250 kg/jam - Ramadhan, Alfian; Hermanto, Tino; Nasution, Heri Prinando (CV. IRA PUBLISHING, 2024)
Plastic waste, which is difficult to decompose, poses a significant environmental hazard. This study aims to analyze the effect of filter diameter on shredding outcomes of a 250 kg/hour plastic shredding machine. Experimental methods were used with HDPE and PP plastics and filter diameters of 16 mm and 20 mm. Results showed that the 16 mm filter yielded better efficiency for HDPE at 82.08%, while the 20 mm filter achieved the highest efficiency at 167.4% for HDPE. For PP, the 20 mm filter yielded the highest efficiency at 44.88%. The findings highlight that filter diameter significantly affects machine performance, with optimal results observed with the 20 mm filter for HDPE.